2014
DOI: 10.3906/bot-1305-52
|View full text |Cite
|
Sign up to set email alerts
|

SEM analysis of the epibenthic diatoms on Eudendrium racemosum (Hydrozoa) from the Mediterranean Sea

Abstract: IntroductionBenthic diatoms of shallow coastal marine areas give a reliable contribution to the dynamics of aquatic ecosystems in terms of primary production, nutrient fluxes, and roles in the trophic web (MacIntyre et al., 1996;Totti, 2003). Communities of benthic diatoms can develop associated to different substrata, from the soft bottom (epipelon, epipsammon, and endopelon) (Totti, 2003) to rocks (epilithon) (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 73 publications
1
11
1
Order By: Relevance
“…In our study, the most frequent Mastogloia was M. cyclops which has been characterized as good indicator of coastal zones (Wachnicka et al, 2010). Some taxa (e.g., C. scutellum, Halamphora coffeiformis) were found on different substrata and do not seem to have a preference either for geographic region or for the substrate type (Romagnoli et al, 2014). By contrast, C. scutellum is considered as typical epiphytic taxon (Ulanova & Snoeijs, 2006).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In our study, the most frequent Mastogloia was M. cyclops which has been characterized as good indicator of coastal zones (Wachnicka et al, 2010). Some taxa (e.g., C. scutellum, Halamphora coffeiformis) were found on different substrata and do not seem to have a preference either for geographic region or for the substrate type (Romagnoli et al, 2014). By contrast, C. scutellum is considered as typical epiphytic taxon (Ulanova & Snoeijs, 2006).…”
Section: Discussionmentioning
confidence: 79%
“…Additionally, it has been pointed out that some taxa may exhibit more than one growth form, reflecting the different strategies of spatial utilization (cf. Romagnoli et al, 2014, and references therein) adopted for the competitive advantage they provide. In this study, although he samples contained a mixture of forms growing on the stones and some epiphytic forms, we refer to this collective community as epilithon (sensu Çolak Sabanci, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sci., 19/2, 2018, 223-239 233 Chen et al, 2010;De Stefano et al, 2000Korte & Blinn, 1983;Round et al, 1961;Siqueiros-Beltrones et al, 1985;Sullivan, 1978Sullivan, , 1984Totti et al, 2007Totti et al, , 2009Wuchter et al, 2003). Romagnoli et al (2014) also suggest that these taxa do not seem to have a preference either for geographic region or for the type of substrate. Cocconeis scutellum was defined as typical epiphytic taxon (Ulanova & Snoeijs, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…In the Mediterranean, several studies, in both heavily urbanized and undisturbed areas, have dealt with the composition of diatom populations grown on artificial (Munda, 2005;Totti et al, 2007) or natural substrates (Facca et al, 2002;Facca & Sfriso, 2007;Çolak Sabanci & Koray, 2010;Çolak Sabanci, 2011Çolak Sabanci, , 2012Cibic & Facca, 2010 and references therein). Many more studies have been reported on diatom epibenthic communities on macroalgae and seagrasses (epiphyton) (Car et al, 2012;De Stefano et al, 2000) or animals (epizoon) (Romagnoli et al, , 2014 and references therein). Most recently, Álvarez-Blanco & Blanco (2014) contributed to knowledge on benthic diatom taxa in Mediterranean, including some Adriatic sites.…”
Section: Introductionmentioning
confidence: 99%